MEDICAL STUDENTS PERCEPTIONS OF THE TRUWINIST INTERDIGITAL METHOD FOR ANTIBIOTIC LEARNING - Trully Deti Rose Sitorus; Fadla Khairatu Ismi; Julia Ramadhanti; Muhammad Hasan Bashari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: The field of education began to shift from conventional methods to the e-learning method. Blended-learning method is a method that combines e-learning and conventional methods. Truwinist Interdigital Method (MTI) is a learning innovation using the blended-learning method. The aim of this study was to determine student perceptions about blended-learning: Truwinist Interdigital Method.Methods: This study is a descriptive studies. The subjects of this study were students of the Medical Undergraduate Study Program of Padjadjaran University in 7th semester, add up to 156 students in total. Subjects were presented with material for 4 days by accessing MTI antibiotics and continued face to face for 1 hour on the fourth day. The research instrument in the form of a questionnaire consisted of 16 statements with 4 aspects of assessment, namely ‘students interest’, ‘accessibility’, ‘content’, and ‘discussion activities in MTI’. The calculation method used likert-scale with index interval analysis.Results: Based on the analysis of the data from questionnaire, all items for aspects of students interest in blended-learning and accessibility were categorized as 'strongly agree'. Index number for the aspect of content is 78.21%; 79.97%; 79.97%; and 82.85% were categorized as 'strongly agree' and 72.28% were categorized as 'agree'. The index number per item for the aspect of discussion activities is 79.65% and 90.54% which is categorized as 'strongly agree', while the index number of 69.55% is categorized as 'agree'.Conclusion: The majority of students have a positive response to learning using blended learning: MTI. Keywords: perception, blended-learning, truwinist interdigital.